Atomic dynamics transition in a Cu-Zr-Al metallic glass. (September 2020) - Wang, X.D.; Xu, T.D.; Su, Y.; Tang, Y.; Sprung, M.; Cao, Q.P.; Zhang, D.X.; Jiang, J.Z.
Abstract: We reveal a slow-to-fast dynamics transition in the as-cast Cu46 Zr46 Al8 (at.%) metallic glass (MG) at a temperature below the glass transition upon heating, which depends on the competition between free volume annihilation and thermally-activated atomic mobility, well consistent with the bond-length change of Cu-Cu pairs. The activation of α -relaxation at high temperatures could be related to the bond-length extension of Cu-Cu and Zr-Zr like-atom pairs together with the shortening of Cu-Zr unlike-atom pairs. Our results provide new insights into the correlation of dynamics with atomic structure in MGs and will be helpful to the understanding of ageing behaviors in MGs. Graphical Abstract: Image, graphical abstract